The textbook in curriculum development – perceptions of students and academics - Martins, Nico (South African Journal of Higher Education, 2016)
One of the initiatives that universities worldwide embark on is to investigate students’ dependence on textbooks and the strengthening of professional control and academics’ reliance on textbooks. The purpose of this research was to determine to what extent academics in South Africa use the textbook in curriculum development and teaching as perceived by academics and students. Academics and students from most of the academic institutions in South Africa participated in the survey-based research. The results indicate a strong reliance on the textbook as a teaching resource with limited differences between Unisa (the University of South Africa), as an ODL institution, and the more traditional universities. The research also indicated a strong relationship between the perceptions of academics and students regarding the use and characteristics of textbooks. The results offer a number of proposals for the use and development of textbooks and supporting resources as additional methods to facilitate learning.